1H-NMR-Based Endometabolome Profiles of Burkholderia cenocepacia Clonal Variants Retrieved from a Cystic Fibrosis Patient during Chronic Infection - Moreira, Ana S.; Lourenço, Artur B.; Sá-Correia, Isabel (Frontiers in Microbiology, 2016)
During cystic fibrosis (CF) chronic lung infections, bacteria of the Burkholderia cepacia complex (Bcc) are exposed for several years to a stressful and changing environment. These environmental challenges results in genetic changes of the initial infecting strain with the consequent diversification of genotypes and phenotypes. The exploitation of functional and comparative genomic approaches has suggested that such diversification is associated with massive metabolic remodeling but these alterations are poorly understood. In the present work, we have explored a high resolution 1H-NMR-based metabolomic approach coupled to multivariate analysis to compare the endometabolome of three Burkholderia cenocepacia clonal variants retrieved from a CF patient from the onset of infection (IST439) until death with cepacia syndrome after 3.5 years (IST4113 and IST4134), to complement former proteomic and transcriptomic analyses. A fourth clonal variant (IST4129) retrieved from the same CF patient when the clinical condition worsened during the last months of life, was also examined since it was found to lack the third replicon. The metabolomic profiles obtained, based on the complete 1H-NMR spectra, highlight the separation of the four clonal variants examined, the most distinct profile corresponding to IST4129. Results indicate a variable content of several amino acids in the different isolates examined and suggest that glycolysis and the glyoxylate shunt are favored in late variants. Moreover, the concentration of two metabolites with demonstrated cellular protective functions against stress, glycine-betaine and trehalose, is different in the different isolates examined. However, no clear correlation could be established between their content and stress tolerance. For example, IST4113, previously found to be the most resistant variant to antimicrobials of different classes, exhibits low levels of trehalose and glycine-betaine but the highest resistance to heat and oxidative stress. Also, IST4129, with a high level of glycine-betaine but lacking the third replicon, previously associated with stress resistance and virulence, exhibits the highest susceptibility to all the stresses tested. Taken together, results from this study provide insights into the metabolic diversification of B. cenocepacia clonal variants during long-term infection of the CF airways.